2016
DOI: 10.1007/s13592-016-0473-3
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachtin-induced antifeeding in Neotropical stingless bees

Abstract: The ongoing debate regarding the role of pesticides in the global decline of bee populations is increasing the demand for use of biopesticides, compounds generally believed to be less harmful to pollinators. However, there is lack of evidence justifying such perceptions, particularly regarding native pollinator species like Neotropical stingless bees. Here, we investigated whether azadirachtin, a neem-based biopesticide, causes significant lethal and sublethal effects on adult workers of the Neotropical stingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
1
21
0
3
Order By: Relevance
“…Previously, azadirachtin was reported to impair, with variable effects, the survival of different insect species . Strong variations in insects' susceptibility to azadirachtin were noted depending on insect order, species, formulation, or the method of application . Sensitivity of insects to insecticides varies also with the regulation of plasma membrane receptor and/or ion channels, penetration rate through the cuticle, absorption by insects, transport in tissues of the body and metabolism …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, azadirachtin was reported to impair, with variable effects, the survival of different insect species . Strong variations in insects' susceptibility to azadirachtin were noted depending on insect order, species, formulation, or the method of application . Sensitivity of insects to insecticides varies also with the regulation of plasma membrane receptor and/or ion channels, penetration rate through the cuticle, absorption by insects, transport in tissues of the body and metabolism …”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported various effects of neem products on non‐target species, such as mites, parasitoids and bees . For example, behaviour and morphological alterations have been highlighted in bees, while Bernades et al . did not detect any effect on worker bee mortality, flight, or respiration rate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limonoids and especially azadirachtin have been found to have subtle growth-disrupting effects on diverse insect pests (Abdelgaleil & Nakatani, 2003;Bilker et al, 2002;Ndung'u et al, 2004;Gonçalves-Gervásio & Vendramim) but non-toxic to mammal cells (Arona et al, 2004). However, the currently most used limonoid-based insecticide, azadirachtin, can compromise the fertility of insect natural enemies of pests, such as those attacking T. absoluta (Biondi, Desneux, Siscaro, & Zappalà, 2012;Biondi et al, 2013), and affect the behaviour of pollinators (Barbosa, De Meyer, Guedes, & Smagghe, 2014;Bernardes, Tomé, Barbosa, Guedes, & Lima, 2017). Therefore, before proposing the use of these new chemicals in Integrated pest Management Programs, comprehensive analyses of the potential non-target effects on beneficial organisms should be carried out.…”
Section: Discussionmentioning
confidence: 99%